Patulin in food: A mycotoxin concern for human health and its management strategies. (30th July 2021) - Mahato, Dipendra Kumar; Kamle, Madhu; Sharma, Bharti; Pandhi, Shikha; Devi, Sheetal; Dhawan, Kajal; Selvakumar, Raman; Mishra, Diwakar; Kumar, Arvind; Arora, Shalini; Singh, Namita Ashish; Kumar, Pradeep
Abstract: The mycotoxin patulin is primarily produced as a secondary metabolite by numerous fungal species and predominantly by Aspergillus, Byssochlamys, and Penicillium species. It is generally associated with fungal infected food materials. Penicillium expansum is considered the only fungal species liable for patulin contamination in pome fruits, especially in apples and apple-based products. This toxin in food poses serious health concerns and economic threat, which has aroused the need to adopt effective detection and mitigation strategies. Understanding its origin sources and biosynthetic mechanism stands essential for efficiently designing a management strategy against this fungal contamination. This review aims to present an updated outline of the sources of patulin occurrence in different foods and their biosynthetic mechanisms. It further provides information regarding the detrimental effects of patulin on human and agriculture as well as its effective detection, management, and control strategies. Graphical abstract: Image 1 Highlights: Patulin is mainly produced by Aspergillus, Byssochlamys, and Penicillium species. Patulin contaminates pome fruits, especially apples and apple-based products. Patulin contaminated products have serious human health impacts. Management strategies are required for the safety and security of food.